IMPOLITENESS STRATEGIES IN YOUTUBE COMMENT SECTION FOUND IN INDONESIAN PRESIDENTIAL DEBATE 2019 - Arrasyd Arrasyd; Hamzah Hamzah (Universitas Negeri Padang, 2019)
The purpose of this study was to find impoliteness strategies used by netizens to Jokowi-Maaruf and netizens to Prabowo-Sandi based on gender in YouTube comments section based on Culpeper`s theory (1996). This research was descriptive qualitative research based on impoliteness strategies phenomena in written language. The data on this research were words, phrases, and sentences in online comments that contained impoliteness strategies found in Indonesian Presidential debate 2019 in YouTube comment. The instruments of this research were Wi-Fi, laptop, writing equipment, and indicators of impoliteness strategies. The results of analysis showed that from 200 comments collected, there were 267 impoliteness strategies found. The reason why number of strategies found bigger than the data collected is because the commentators mostly performed more than one strategy in one utterance. Four by five strategies found in this research were bald on record, positive impoliteness, negative impoliteness, and sarcasm or mock politeness. The strategies that were not found ware withhold politeness because it only occurred in spoken language. The most used strategies were positive impoliteness. The highest user of positive impoliteness was male netizens to female netizens to Prabowo-Sandi (47%).